Novel Pastes Containing Polymeric Nanoparticles for Dentin Hypersensitivity Treatment: An In Vitro Study - Manuel Toledano-Osorio (MDPI AG, 2021)
Tubule occlusion and remineralization are considered the two main goals of dentin hypersensitivity treatment. The objective is to assess the ability of dentifrices containing zinc-doped polymeric nanoparticles (NPs) to enduringly occlude the dentinal tubules, reinforcing dentin’s mechanical properties. Fifteen dentin surfaces were acid-treated for dentinal tubule exposure and brushed with (1) distilled water, or with experimental pastes containing (2) 1% of zinc-doped NPs, (3) 5% of zinc-doped NPs, (4) 10% of zinc-doped NPs or (5) Sensodyne®. Topographical and nanomechanical analyses were performed on treated dentin surfaces and after a citric acid challenge. ANOVA and Student–Newman–Keuls tests were used (p < 0.05). The main results indicate that all pastes produced tubule occlusion (100%) and reinforced mechanical properties of intertubular dentin (complex modulus was above 75 GPa). After the citric acid challenge, only those pastes containing zinc-doped NPs were able to maintain tubular occlusion, as specimens treated with Sensodyne® have around 30% of tubules opened. Mechanical properties were maintained for dentin treated with Zn-doped NPs, but in the case of specimens treated with Sensodyne®, complex modulus values were reduced below 50 GPa. It may be concluded that zinc-doped NPs at the lowest tested concentration produced acid-resistant tubular occlusion and increased the mechanical properties of dentin.